Technology in the Creative Economy: Implications for Community Empowerment and Sustainable Development - Mubarok, Djihadul; Muhamad, Lili Fadli; Kusuma, Aditya Putra (PT. LITERASI SAINS NUSANTARA, 2024)
In recent decades, the creative economy has emerged as one of the most dynamic and rapidly growing sectors globally, including in Indonesia. This sector encompasses various industries that focus on creating economic value through creativity, innovation, and the exploitation of intellectual property. Technology plays a crucial role in supporting the growth of the creative economy, from product development to distribution and marketing. This study aims to explore the implications of technology in the creative economy for community empowerment and sustainable development. The research method employed is a literature review with a qualitative approach. Research data was collected from Google Scholar for the period 2016-2024. The study's results show that technology plays a critical role in supporting and developing the creative economy sector, particularly in the context of community empowerment and sustainable development. Technology has enabled broader access to global markets, driven product and service innovation, and strengthened the preservation and promotion of local cultural heritage. Case studies from various regions in Indonesia, such as Bandung and Yogyakarta, demonstrate how technology can be used to empower local communities and support inclusive and environmentally friendly economic development.